Uncovering a 500 million year old history and evidence of pseudogenization for TLR15 - Neves, Fabiana; Muñoz-Mérida, Antonio; Machado, André M.; Almeida, Tereza; Gaigher, Arnaud; Esteves, Pedro J.; Castro, L. Filipe C.; Veríssimo, Ana (Frontiers in Immunology, 2022)
Toll like receptors (TLRs) are at the front line of pathogen recognition and host immune response. Many TLR genes have been described to date with some being found across metazoans while others are restricted to specific lineages. A cryptic member of the TLR gene family, TLR15, has a unique phylogenetic distribution. Initially described in extant species of birds and reptiles, an ortholog has been reported for cartilaginous fish. Here, we significantly expanded the evolutionary analysis of TLR15 gene evolution, taking advantage of large genomic and transcriptomic resources available from different lineages of vertebrates. Additionally, we objectively search for TLR15 in lobe-finned and ray-finned fish, as well as in cartilaginous fish and jawless vertebrates. We confirm the presence of TLR15 in early branching jawed vertebrates – the cartilaginous fish, as well as in basal Sarcopterygii – in lungfish. However, within cartilaginous fish, the gene is present in Holocephalans (all three families) but not in Elasmobranchs (its sister-lineage). Holocephalans have long TLR15 protein sequences that disrupt the typical TLR structure, and some species display a pseudogene sequence due to the presence of frameshift mutations and early stop codons. Additionally, TLR15 has low expression levels in holocephalans when compared with other TLR genes. In turn, lungfish also have long TLR15 protein sequences but the protein structure is not compromised. Finally, TLR15 presents several sites under negative selection. Overall, these results suggest that TLR15 is experiencing ongoing pseudogenization in early-branching vertebrates.